Robot-assisted endoscopic inguinal lymphadenectomy: A review of current outcomes - Gilberto José Rodrigues; Giuliano Betoni Guglielmetti; Marcelo Orvieto; Kulthe Ramesh Seetharam Bhat; Vipul R. Patel; Rafael Ferreira Coelho (Asian Journal of Urology)
Objective: To review the role of robot-assisted endoscopic inguinal lymphadenectomy (RAIL) in the management of penile cancer. Methods: A PubMed search for all relevant publications regarding RAIL series up until August 2019 was performed using the keyword “robotic”, “inguinal lymph node dissection”, and “penile cancer”. Weighted mean was calculated in the largest series for all outcomes using the number of patients included in each study as the weighting factor. Results: We identified 23 articles, of note the three largest series that included 102, 27, and 20 RAIL in 51, 14, and 10 patients, respectively. Saphenous vein was spared in 88.93% of RAIL cases in these series and node yield was 11.42 per groin; 35.28% of patients had positive pathological nodes. The weighted mean of operative time was 87.98 min per RAIL and the estimated blood loss was 37.08 mL per patient. The mean length of hospital stay was 1.29 days and the drain was kept in place for 17.02 days; the major complication rate was only 5.31% in these series. The mean follow-up was 33.46 months with a recurrence-free survival of 96.33%. Conclusion: The literature regarding RAIL describes promising results, although it has shorter follow-up and higher costs when compared to historically series from the open approach. Initials series reported lower cutaneous complications compared to conventional approach, without compromising oncological outcomes. However, long-term results and larger trials are crucial to validate those findings.